Aplikasi Vermikompos dan Pupuk NPK 16:16:16 terhadap Hasil Tanaman Labu Madu(Cucurbita moschata L.) pada Tanah PMK - Octariani, Diah; Maizar, Maizar (Jurnal Agroteknologi, Agribisnis, dan Akuakultur, 2026)
The research was carried out at the Experimental Garden of the Faculty of Agriculture, Riau Islamic University, Pekanbaru City for 4 months starting from February-May 2023. This research used a Factorial Completely Randomized Design (CRD) consisting of two factors. The first factor is Vermicompost (V) consisting of 5 levels, namely 0, 1, 2, 3, and 4 kg/plot and the second factor is NPK 16:16:16 (N) consisting of 4 levels, namely 0, 7.5, 15, and 22.5 g/plant. The parameters observed were flowering age, harvest age, number of fruits per plant, fruit length, fruit weight per plant, fruit weight per fruit, fruit weight per plot, ratio of male flowers to female flowers and sugar content. The observation data was analyzed statistically and continued with the HSD test at the 5% level. The research results showed that the interaction between Vermicompost and NPK 16:16:16 had a significant effect on the parameters of flowering age, harvest age, fruit length, fruit weight per plant, fruit weight per fruit, fruit weight per plot, ratio of male flowers to female flowers and sugar content. The best combination of 3 kg vermicompost/plot and NPK 16:16:16 dose of 15 g/plant. The main effect of vermicompost and NPK 16:16:16 was significant on the parameters of flowering age, harvest age, fruit length, fruit weight per plant, fruit weight per fruit, fruit weight per plot and sugar content. The best treatment is vermicompost at a dose of 3 kg/plot and NPK 16:16:16 at a dose of 15 g/plant.